2018
DOI: 10.1016/j.jtcvs.2017.12.137
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of expanded polytetrafluoroethylene conduits with bulging sinuses and a fan-shaped valve in right ventricular outflow tract reconstruction

Abstract: The long-term outcomes of the ePTFE conduit with a fan-shaped valve and bulging sinuses appear clinically satisfactory. We believe that the longevity of small-sized conduits can yield sufficient time to exchange them to larger-sized conduits without any loss of their valve functions. Regarding longevity and resistance to infections, this ePTFE valved conduit can be one of the best ways to reconstruct the RVOT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
54
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 16 publications
0
54
0
2
Order By: Relevance
“…In another clinical trial, Miyazaki et al implanted ePTFE valves (monocuspid, bi-leaflet and tri-leaflet) for RVOT in 157 patients (aged 16 days to 45.4 years, median 2 years) [14], and no mortality, morbidity or reoperation were reported during the follow-up period (5.6 to 63.7 months, mean 20.8 months). Moreover, the good biocompatibility of ePTFE artificial heart valves has been verified by several clinical studies [14, 25, 26]. In recent literature, the ePTFE membrane was also selected as the material for aortic valve extension [27].…”
Section: Introductionmentioning
confidence: 99%
“…In another clinical trial, Miyazaki et al implanted ePTFE valves (monocuspid, bi-leaflet and tri-leaflet) for RVOT in 157 patients (aged 16 days to 45.4 years, median 2 years) [14], and no mortality, morbidity or reoperation were reported during the follow-up period (5.6 to 63.7 months, mean 20.8 months). Moreover, the good biocompatibility of ePTFE artificial heart valves has been verified by several clinical studies [14, 25, 26]. In recent literature, the ePTFE membrane was also selected as the material for aortic valve extension [27].…”
Section: Introductionmentioning
confidence: 99%
“…It has good biocompatibility and its surface exerts antithrombogenic effects by electrically repelling platelets. 21,22 The histopathological analysis of explanted ePTFE valved patches or conduits showed that the surface of vascular grafts was covered in thin fibrous collagenous tissue predominantly comprising fibroblasts, even with partial endothelialization, whereas the valvular leaflet remained free of any attached matter. 23 Sasikumar et al 14 We agree with the idea of trying to preserve the integrity of pulmonary annulus and competency of the valve in all patients with TOF during repair but it is not always possible.…”
Section: Discussionmentioning
confidence: 99%
“…Among the newly proposed alternatives, the pulmonary valve prostheses made of the expanded-polytetrafluoroethylene (ePTFE) membrane have attracted great interest. The ePTFE is an inert material with microporous structure, which not only has good biocompatibility but also prevents the inflammation, calcification, and cell penetration that contribute to the valve deterioration (Zhu et al, 2015;Miyazaki et al, 2018;Sharifulin et al, 2018). Since Yamagishi et al, 1998 reported their early experiences (Yamagishi and Kurosawa, 1993), prosthetic pulmonary valves made of the ePTFE membrane have been widely used for PVR and RVOT in several centers in Japan and the United States.…”
Section: Introductionmentioning
confidence: 99%
“…The follow-up results of the implantations of ePTFE prosthetic pulmonary valve have shown promising mid-to long-term outcomes. For the prostheses with trileaflet designs that mimic the native pulmonary valve configuration, the re-intervention rate at 5 years and 10 years was 7.7 and 23.9%, respectively (Brown et al, 2007;Miyazaki et al, 2018). In addition to the trileaflet design, the ePTFE valves with monoleaflet and bileaflet designs were also introduced to adapt the smaller pulmonary conduit size of pediatric patients as well as simplify the preparation procedures in the operation room (Yamagishi and Kurosawa, 1993;Quintessenza, 2014;Ootaki and Williams, 2018).…”
Section: Introductionmentioning
confidence: 99%